Manasa tattva and it’s chikitsa siddhanta , explained in ayurveda.: Manasa tattva and it’s chikitsa siddhanta , explained in ayurveda. - sudhalokhande (Ayurline: International Journal of Research in Indian Medicine, 2021)
Manas roga in modern age are known as psychiatric diseases & treatment with Ayurvedic principals is known as Ayurvedic psychotherapy. The study of mental health constitutes one of the eight division of Ayurveda. Underlying pathology of manasa roga is psychological or emotional imbalance. Physical diseases are outcome of psychological factors. It is seen that patients are careless about mental & physical health as they are preoccupied by psychological imbalance. According to manovigyana, site of mind is heart. Manasa rog are associated with emotional trauma, negative attitude, stress. According to Ayurveda manasa roga are born out of disturbance in satwa guna. In Ayurveda Chikitsa is classified into 3 types Daivavyapashraya Chikitsa (divine therapy), Yuktivyapashraya Chikitsa (rational therapy) and Satvavajaya Chikitsa (psychotherapy). Daivavyapashraya Chikitsa involvesmeasures to combat Daivakrit diseases. Yuktivyapasraya is treatment based on fundamental principles of Ayurveda. Sattvavajaya Chikitsa is to control the mind by withdrawing it from undesired objects. Ayurveda gives more stress to Sattvvajaya Chikitsa and Daivavyapashraya Chikitsa in managing manovikaras. This article will help readers to understand role of Ayurveda in maintaining Manasika Swasthyam. Key words:- Manas rog, Daivavyapashraya, Yuktivyapasraya, Sattvvajaya, Chikitsa